Educational Gerontology and Historically Black Colleges and Universities - Onna T Jordan Ms (Adult Education Research Conference, 2017)
Older adult learners account for a significant percentage of the educational market, forcing educational institutions to identify and adjust educational programs to reflect older learners needs, outcomes, and motives.
Keywords: Gerontology; Motivations; Enculturation; Professional Development; HBCU